2018
DOI: 10.1002/1878-0261.12178
|View full text |Cite
|
Sign up to set email alerts
|

STAT1 is a sex‐specific tumor suppressor in colitis‐associated colorectal cancer

Abstract: The interferon‐inducible transcription factor STAT1 is a tumor suppressor in various malignancies. We investigated sex‐specific STAT1 functions in colitis and colitis‐associated colorectal cancer (CRC) using mice with specific STAT1 deletion in intestinal epithelial cells (STAT1∆IEC). Male but not female STAT1∆IEC mice were more resistant to DSS‐induced colitis than sex‐matched STAT1flox/flox controls and displayed reduced intraepithelial infiltration of CD8+ TCRαβ+ granzyme B+ T cells. Moreover, DSS treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
23
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 47 publications
2
23
1
Order By: Relevance
“…Here, this study revealed that CH25H participates in the pathophysiology of colitis in mice through its protective and anti-inflammatory roles. This observation is in contrast with the findings of a recent study that showed no effect in DSS-treated Ch25h −/− mice 36 . We suspect that there are two main explanation for this inconsistency.…”
Section: Discussioncontrasting
confidence: 99%
“…Here, this study revealed that CH25H participates in the pathophysiology of colitis in mice through its protective and anti-inflammatory roles. This observation is in contrast with the findings of a recent study that showed no effect in DSS-treated Ch25h −/− mice 36 . We suspect that there are two main explanation for this inconsistency.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, the neoplastic and immunological consequences of epithelial Stat1 deletion in CAC are different from sporadic CRC. We found increased AOM-DSS-induced CAC formation in male Stat1 ΔIEC mice 64 . Stat1 ΔIEC tumors contained reduced numbers of CD8 + T cells 64 , although IDO1 + Paneth cells were absent (unpublished data).…”
Section: Discussionmentioning
confidence: 58%
“…We found increased AOM-DSS-induced CAC formation in male Stat1 ΔIEC mice 64 . Stat1 ΔIEC tumors contained reduced numbers of CD8 + T cells 64 , although IDO1 + Paneth cells were absent (unpublished data). Therefore, Stat1-dependent IDO1 + Paneth cells might be particularly important for the development of sporadic tumors but dispensable for CAC.…”
Section: Discussionmentioning
confidence: 58%
“…Our present study further sheds light on the role of STAT3 signaling in K-ras mutant lung cancer pathogenesis by highlighting stark sex disparity in this process and showing, in contrast, attenuated tumorigenesis in female mice with Stat3 deletion. It is important to note that the report by Crncec and colleagues demonstrated sex-specific tumor suppressor and anti-tumor immune roles for another Stat, Stat1 , in colitis-associated colorectal cancer in male but not female mice 43 . Our findings suggest that, similar to Stat1 43 , epithelial Stat3 may exhibit sex-specific lung tumor suppressor roles in males.…”
Section: Discussionmentioning
confidence: 98%
“…It is important to note that the report by Crncec and colleagues demonstrated sex-specific tumor suppressor and anti-tumor immune roles for another Stat, Stat1 , in colitis-associated colorectal cancer in male but not female mice 43 . Our findings suggest that, similar to Stat1 43 , epithelial Stat3 may exhibit sex-specific lung tumor suppressor roles in males.…”
Section: Discussionmentioning
confidence: 98%